Reducing bubbles in friction lap welded joint of magnesium alloy and polyamide. (October 2014) - Liu, F. C.; Nakata, K.; Liao, J.; Hirota, S.; Fukui, H.
<x content-type="archive" xml:space="preserve">Abstract</x> The direct joining between AZ31B Mg alloy and MC Nylon 6 using friction lap welding (FLW) was performed over a wide range of welding parameters to clarify the effect of welding parameters on bubble formation for the purpose of obtaining high strength hybrid joints without bubbles. The volume of bubbles in the FLW joints was influenced by the amount of gases generated due to the pyrolysis of Nylon 6 and the amount of gases squeezed out of the joints during welding. An appropriate increase in welding speed, tool rotation rate and plunge depth can reduce the volume of bubbles. Strong FLW joint with area fraction of bubbles <8% was obtained after welding process optimisation.